2022
DOI: 10.3390/antiox11050935
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Attenuates Oxidative Stress, Inflammation, and Apoptosis Induced by Acute Hypoxia through the Nrf2/Keap1 Signaling Pathway in Gibel Carp (Carassius gibelio)

Abstract: Previous studies have found that vitamin C (VC) has protective effects in fish. However, the efficacy of VC on hypoxia-induced liver injury in fish remains unknown. Therefore, to investigate the protective mechanism of VC on liver injury after acute hypoxic stimulation in fish, gibel carp were fed a diet containing VC for eight weeks, then were subjected to acute hypoxia stimulation. The specific growth rate of fish was increased by the supplementation of VC. Plasma stress markers (glucose, lactic acid, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 53 publications
1
13
1
Order By: Relevance
“…In addition to GSH, ALA and other antioxidants were significantly decreased in the serum of HAPE model rats. Interestingly, however, VC levels, which have strong antioxidant capacity, increased in rats after hypoxia stimulation, which is inconsistent with some previous research results ( Sureda et al, 2004 ; Wu et al, 2022 ). This may be related to the long half-life of VC and adaptive regulation of the body; however, further studies are needed to clarify this.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to GSH, ALA and other antioxidants were significantly decreased in the serum of HAPE model rats. Interestingly, however, VC levels, which have strong antioxidant capacity, increased in rats after hypoxia stimulation, which is inconsistent with some previous research results ( Sureda et al, 2004 ; Wu et al, 2022 ). This may be related to the long half-life of VC and adaptive regulation of the body; however, further studies are needed to clarify this.…”
Section: Discussioncontrasting
confidence: 99%
“…The concentrations of glucose and lactic acid in serum are readily affected by external pressure. Hypoxia leads to stress in fish: there is a change from aerobic metabolism to anaerobic metabolism, and anaerobic glycolysis increases, resulting in the accumulation of lactic acid in serum [36,37]. In the present study, we found that blood glucose levels were lower in the hypoxia-treated group than in the control group.…”
Section: Discussionsupporting
confidence: 48%
“…The biochemical analysis was conducted based on reported methods [ 28 ]. The ALT and AST in plasma and the MDA, SOD, and GPx in the liver were determined using assay kits (Nanjing Jiancheng Bioengineering Institute; Catalog: C009-2-1, C010-2-1, A003-1, A001-3, and A005-1, Jiangsu, China).…”
Section: Methodsmentioning
confidence: 99%